Velocity-Based Resistance Training Monitoring: Influence of Lifting Straps, Reference Repetitions, and Variable Selection in Resistance-Trained Men - Jukic, Ivan; García-Ramos, Amador; Tufano, James J (Sports health, 2023)
BACKGROUND: Using lifting straps during pulling exercises (such as deadlift) may increase absolute velocity performance. However, it remains unclear whether lifting straps could also reduce the degree of relative fatigue measured by velocity decline and maintenance in a training set. HYPOTHESIS: There will be less mean velocity decline (MVD) and greater mean velocity maintenance (MVM) for deadlifts performed with (DLw) compared with without (DLn) lifting straps, and an underestimation of MVD and MVM when using the first compared with the fastest repetition as a reference repetition. STUDY DESIGN: Randomized cross over design. LEVEL OF EVIDENCE: Level 3. METHODS: A total of 16 resistance-trained men performed a familiarization session, 2 1-repetition maximum [1RM] sessions (1 with and 1 without lifting straps), and 3 randomly applied experimental sessions consisting of 4 sets of 4 repetitions: (1) DLw against the 80% of DLn 1RM (DLwn), (2) DLn against the 80% of the DLn 1RM (DLnn), and (3) DLw against the 80% of the DLw 1RM (DLww). MVD and MVM were calculated using the first and the fastest repetition as the reference repetition. RESULTS: MVD was significantly lower during DLwn and DLnn compared with DLww (P < 0.01), whereas MVM was greater during DLwn and DLnn compared with DLwn (P < 0.01) with no differences between DLwn and DLnn for both MVD and MVM (P > 0.05). The second repetition of the set was generally the fastest (54.1%) and lower MVD and higher MVM were observed when the first repetition was used as the reference repetition (P < 0.05). CONCLUSION: Lifting straps were not effective at reducing MVD and increasing MVM when the same absolute loads were lifted. Furthermore, using the first repetition as the reference repetition underestimated MVD, and overestimated MVM. CLINICAL RELEVANCE: The fastest repetition should be used as the reference repetition to avoid inducing excessive fatigue when the first repetition is not the fastest.
Keywords: Male; únava; odporový trénink; fatigue; Muscle, Skeletal; mužské pohlaví; Resistance Training; svalová síla; kosterní svaly; Muscle Strength; lidé; Humans; training prescription; vzpírání; Fatigue; monitoring; Weight Lifting; resistance training; velocity